Cancer nanoimmunotherapy using advanced pharmaceutical nanotechnology. (November 2014) - Li, Wei; Wei, Huafeng; Li, Huafei; Gao, Jie; Feng, Si-Shen; Guo, Yajun
Immunotherapy is a promising option for cancer treatment that might cure cancer with fewer side effects by primarily activating the host's immune system. However, the effect of traditional immunotherapy is modest, frequently due to tumor escape and resistance of multiple mechanisms. Pharmaceutical nanotechnology, which is also called cancer nanotechnology or nanomedicine, has provided a practical solution to solve the limitations of traditional immunotherapy. This article reviews the latest developments in immunotherapy and nanomedicine, and illustrates how nanocarriers (including micelles, liposomes, polymer–drug conjugates, solid lipid nanoparticles and biodegradable nanoparticles) could be used for the cellular transfer of immune effectors for active and passive nanoimmunotherapy. The fine engineering of nanocarriers based on the unique features of the tumor microenvironment and extra-/intra-cellular conditions of tumor cells can greatly tip the triangle immunobalance among host, tumor and nanoparticulates in favor of antitumor responses, which shows a promising prospect for nanoimmunotherapy.